Avaliação do desenvolvimento infantil de crianças moradoras de comunidades em vulnerabilidade social de Maceió-AL - Camilo, Lara dos Santos (2018)
Studies have shown that greater attention in early childhood brings benefits that last for life, health, learning, autonomy and social participation. Events that occur early in life affect brain configurations such as brain changes resulting from conditions of social vulnerability, decreased attachment to the mother, poor nutrition, and maltreatment that can lead to permanent changes in child development. Child development is a process of maturation and interaction, resulting in an orderly progression of perceptions, motor activities, cognitive, language, emotional partner and self-regulation. In medium / low income and higher vulnerability countries, around 250 million children under the age of five are at risk of not growing and developing properly. In Brazil, according to IBGE, approximately 16.7 million people live in extreme poverty, of which 9.6 million are in the Northeast. The state of Alagoas, in turn, is one of those with the highest percentage of municipalities with high social vulnerability index, reaching 95.4%. This state of vulnerability ends up affecting the mother / child bond, health, psychological, social, mental and nutritional status of children, preventing these children from reaching their full potential for child development. The brain is a complex organ and is not yet complete at birth and the first two years of life are essential for its formation. At birth a baby's brain weight corresponds to 25% of an adult's, at two years it reaches 75%, and the number of synapses multiplies to 700 new synapses per second at two years, brain plasticity is also which increases the capacity for transformation to stimuli and lived experiences. It is also known that early childhood development reflects in schooling, in the subsequent stages and in their professionalization as an adult. In this way, assessing child growth is imperative so that early interventions can be made before the delay is finally established, but measuring the outcomes of child development in very young children and large samples is still a challenge, however, multi-dimensional screeners offer reliable alternatives. Among them, the Denver-II screen is the multi-dimensional test that has proven to be the most viable and validated in several countries in the world, including Brazil.